Urban Planning from a City Design Perspective: Thoughts on Refined Management - Xu, Xiangdong (Transactions on Economics, Business and Management Research, 2024)
The importance of city design in urban planning and construction is self-evident. It not only carries the mission of shaping the urban image and enhancing the quality of the city but also acts as a compass for the future direction of urban development. It plays an irreplaceable role in improving the level of urban planning, meeting the demands of urban development, and adapting to the overall socio-economic development level. With the acceleration of urbanization, city design is no longer a simple layout of buildings and space division. Instead, it requires a comprehensive consideration of economic, social, cultural, environmental, and other factors to achieve sustainable urban development. Therefore, based on the perspective of city design, strengthening the refined management of urban planning has become an important topic in the field of urban planning. The concept of refined management emphasizes control over details and optimization of the process. Integrating this concept into every aspect of urban planning can significantly improve the scientific and practical effectiveness of urban planning. In the process of city design, meticulous planning and design for every inch of land, every building, and every street ensure they meet people's daily needs, reflect the city's cultural heritage and distinctive features, satisfy people's longing for a better life, and inject new vitality into the city's prosperity and development.